Predictors of Fatal Pulmonary Haemorrhage in Dogs Affected by Leptospirosis Approaching Haemodialysis - Ilaria Lippi; Caterina Puccinelli; Francesca Perondi; Gianila Ceccherini; Alessio Pierini; Veronica Marchetti; Simonetta Citi (Veterinary Sciences, 2021)
A retrospective case control study, which aimed to evaluate potential clinical, laboratory and imaging predictors of fatal pulmonary haemorrhage in dogs with Leptospirosis submitted to haemodialysis. The study population was divided in two groups according to the presence (PH) or absence (nPH) of pulmonary haemorrhage. A statistical comparison was performed at hospital admission for clinical (spontaneous bleeding, icterus, and respiratory distress), laboratory (serum creatinine, urea, phosphate, calcium, bicarbonate, bilirubin, AST, ALT, ALKP, GGT, total protein, albumin, glycaemia, sodium, potassium, CRP, RBC, HCT, HGB, WBC, PLT, PT, aPTT, fibrinogen), and pulmonary radiographic findings between the two groups of dogs. At hospital admission, dogs developing pulmonary haemorrhage were more likely to have respiratory distress (p = 0.002), severely elevated serum bilirubin (p = 0.002), AST (p = 0.04), ALT (p = 0.012), ALKP (p = 0.002), reduced serum glycaemia (p = 0.014), and thrombocytopenia (p = 0.04). Respiratory distress and elevated serum bilirubin (≥11.5 mg/dL) were independently associated with increased risk of pulmonary haemorrhage. In conclusion, the presence of respiratory distress at hospital admission is strongly associated (OR 40.9) with increased risk of pulmonary haemorrhage, even though no abnormalities are found at chest radiography.